Membangun Kesadaran Publik Anti Korupsi Dalam Konsep Pendidikan Berbasis Agama Islam - Hilmin Hilmin; Dwi Noviani (STIKes Ibnu Sina Ajibarang, 2023)
Build public awareness in the concept of anti-corruption education based on Islam aims to form a generation that has strong moral awareness, an understanding of true Islamic values, and social responsibility towards society in forming honest, just and anti-corruption individuals. Islamic Religion-based education has an important role in building a social order that is based on faith and piety, so that anti-corruption education must be integrated and inclusive in formal education as well as in people's daily lives. The educational process must foster normative social awareness, build objective reasoning, and develop a universal perspective of truth for individuals based on collective religious values ​​in the midst of a predominantly Muslim society in Indonesia. Building massive public awareness by integrating education and social movements, involving media participation, encouraging the implementation of a transparent and accountable government system and rewarding non-corrupt behavior by creating zones of integrity. Religious awareness is certainly the foundation in building collective anti-corruption awareness. By positioning the role of the individual who understands and believes in moral and social responsibility, as well as personal responsibility with God so that every action will be accountable to God and the retribution will be the law of the hereafter.